The microbial production of kynurenic acid using Yarrowia lipolytica yeast growing on crude glycerol and soybean molasses - Rakicka-Pustułka, Magdalena; Ziuzia, Patrycja; Pierwoła, Jan; Szymański, Kacper; Wróbel-Kwiatkowska, Magdalena; Lazar, Zbigniew (Frontiers in Bioengineering and Biotechnology, 2022)
Yarrowia lipolytica yeast are able to produce kynurenic acid - a very valuable compound acting as neuroprotective and antioxidant agent in human. The recent data proved the existence of kynurenine biosynthesis pathway in this yeast cells. Due to that, the aim of this work was to enhance kynurenic acid production using crude glycerol and soybean molasses as cheap and renewable carbon and nitrogen sources. The obtained results showed that Y. lipolytica GUT1 mutants are able to produce kynurenic acid in higher concentrations (from 4.5 mg dm-3 to 14.1 mg dm-3) than the parental strain (3.6 mg dm-3) in supernatant in a medium with crude glycerol. Moreover, the addition of soybean molasses increased kynurenic acid production by wild type and transformant strain. The A-101.1.31 GUT1/1 mutant strain produced 17.7 mg dm-3 of kynurenic acid in supernatant during 150 h of the process and 576.7 mg kg-1 of kynurenic acid in dry yeast biomass. The presented work proves the great potential of microbial kynurenic acid production using waste feedstocks. Yeast biomass obtained in this work is rich in protein, with low content of lipid and can be a healthy ingredient of animals and human diet.